Análise dos rendimentos obtidos no mercado de trabalho por indivíduos graduados da região Sul do Brasil. - Silva, Grazielli Olimpia Viviani Pedroso da (2018)
This work proposes an analysis on the income obtained by undergraduates from the Southern Region of Brazil in the labor market during the year of 2010, based on the Human Capital Theory, which provides a positive approach between education and income, indicating that the higher the level of education of the individual, the higher the wage tends to be in the labor market. In addition to education, other factors are important in determining individual wages, for this, the Theory of Labor Market Segmentation was also used complementarily to the Human Capital Theory. It was sought in the research to verify how the choice for a certain career affects the individual income. In addition, it was investigated the effects of the municipal unemployment rate on individual income, and the impact of individual characteristics on income. It was selected the working individuals who declared to have higher education for the 2010 Census, aged between 18 and 80 years. The method used to work the data was the hierarchical logit model in two levels applied to the micro data of the Demographic Census 2010. At the first level it was used variables that represent individual characteristics of the workers, such as age, color or race, domicile status, whether they work in the formality or not, gender and higher education category; in the second level the variable used was the municipal unemployment rate. In order to work the data and obtain the result of the descriptive statistics and the econometric model, the software Stata 13 was used. The results showed that although higher education positively impacts the income of the worker, there is a differential of income according to the individual higher education degree, medicine is the category of higher education that compared to all other categories has higher income, followed by engineering and dentistry, the category of education is the one with the lowest income compared to all other categories of higher education, it was also verified that there is income inequality between people with higher education according to color or race, gender, domicile status and category of work (formal or informal). The unemployment rate also has an impact on the individual incomes of undergraduate workers. Therefore, one cannot attribute the level of education as determinant of the individual income, but other factors as well, such os its personal characteristics and macroeconomic variables that compose characteristics of the region in which the individual live.